VOTER EDUCATION FOR THE DEAF DURING THE COVID–19 PANDEMIC - Reno Fernandes, Nora Susilawati, Rila Muspita, Eka Vidya Putra, Emizal Amri, Amin Akbar, Aprizon Putra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The election of regional heads in 2020 coincided with the outbreak of the COVID–19 virus in Indonesia. Voter education is an important part that must be implemented in the election phase-only uses socialization through mass media. This condition makes the education of voters less accessible to disability groups especially deaf. This research developed video as a voter education material to the deaf that suits the needs and characteristics of deaf students. The method used is the plomp model development method. Video rating is valid and effective. Validated elements are voter education materials, language, graphics, visual and social media. while the effective element is seen from the pretest and posttest. The results of this study are voter education videos that are made to meet valid and effective criteria so that it can be used for the educational materials of voters to the deaf.